Makroskopik semen segar kambing bangsa Peranakan Etawa (PE), Boer dan Saanen di Balai Inseminasi Buatan Lembang - Mokoagow, F.; Pudjihastuti, E.; Hendrik, M.J; Paputungan, U. (Universitas Sam Ratulangi, 2021)
MACROSCOPIC TEST OF FRESH SEMEN IN GOAT BREEDS OF ETTAWAH, BOER AND SAANEN AT LEMBANG ARTIFICIAL INSEMINATION CENTER. Research aim to evaluate the macroscopic quality of fresh semen in goat breeds of Ettawah, Boer and Saanen at Lembang Artificial Insemination Center. Direct observation was done to obtain primer data. Secondary data were found as additional data supporting primer data. Variables included in observation were involving semen volume, ejaculates, color, consistence, pH and smell. Semen qualities of three breed groups collected on three sequent months were analyzed by t-test method. Results showed that semen qualities for ejaculates from three breed groups of Ettawah, Boer and Saanen collected on different months of September, October and November were not significantly different with the averages of 2.47 ml, 2.64 ml and 2.70 ml respectively. Semen volume from three breed groups of Ettawah, Boer and Saanen collected on those different months were also not significantly different with the averages of significantly different with the averages of 2,30 2,64 and 2,60 mL, respectively. The percentages of color of fresh semen from Ettawah, Boer and Saanen collected on those different months were indicating cream of semen collected on September, October in Ettawah Grade, Boer and Saanen. Fresh semen of these breeds was indicating yellow color collected on November, but it was showing normal condition. Fresh semen of these breeds collected on those months were totally indicating thick consistency. However, pH of fresh semen in all three breeds of goat collected on September and October were significantly different with those collected on November. The pH of fresh semen in these breeds collected on September and October were not significantly different. Values of pH in these breeds collected on September, October and November were 6.63, 6.65 and 6.70, respectively. These values were ranging in normal condition. The smell of fresh semen in these breeds collected on those series of months was indicating specific rancid smell.Key words: Fresh semen quality, goat breed, semen collection period